SURGICAL MANAGEMENT OF RUMINAL EVISCERATION THROUGH A DOG BITE WOUND IN A GOAT– A CASE REPORT - S. Kandasamy; P. Sankar; M. Vijayakumar; A. Kumaresan; S. Kathirvel; S. Kokila (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A proper care, prompt reporting and immediate surgical inervention will save the life of the animal. A four year old pluriparous doe was presented with the history of dog bitten wound with eviscerated mass from the injured site at the left lateral aspect of the abdomen. The goat was kept on lateral recumbancy, on clinical examination revealed eviscerated rumen without any lacerations. Surgical area was prepared aseptically, under Inj. Xylazine as premedication and Inj. ketamine and inj. diazepam as induction anaesthesia reconstructive surgery was performed. Rumenotomy was performed to reduce the content and rumen was closed by the two rows of inversion suture. Peritoneum and transverse abdominus muscle were apposed by inversion suture pattern and oblique abdominus internus and externus muscle were apposed by interrupted suture pattern using catgut no 1. Skin was apposed by interupted suture pattern using cotton thread (no 8). Postoperatively Inj. Tetanus toxoid (5 Lfu), ceftriaxone @ 10 mg per kg and meloxicam @ 0.5 mg per kg were given intramuscularly and the animal was maintained with fluid therapy, antibiotic and analgesic for five days and animal recovered after one week.